2005
DOI: 10.1063/1.1825383
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion, relaxation, and chemical exchange in casein gels: A nuclear magnetic resonance study

Abstract: Water in protein/water mixtures can be described in terms of bound water and free water, by exchange between these two states, and by its exchange with appropriate sites on the protein. 1H-NMR diffusion and relaxation measurements provide insights into the mobility of these states. T2 relaxation-time dispersions (i.e., T2 relaxation times at different echo pulse spacings) reveal additional information about exchange. We present a comprehensive set of diffusion and T2 dispersion measurements on casein gels for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 20 publications
0
21
1
Order By: Relevance
“…All these latter works concern however slow exchange (at least with respect to chemical shift). Although a relatively recent publication (14) deals with fast exchange (the topic of the present work), we were unable to find any explanation of our experimental observations in these previous studies.…”
Section: Theorycontrasting
confidence: 54%
“…All these latter works concern however slow exchange (at least with respect to chemical shift). Although a relatively recent publication (14) deals with fast exchange (the topic of the present work), we were unable to find any explanation of our experimental observations in these previous studies.…”
Section: Theorycontrasting
confidence: 54%
“…This confirms the identification of the two signals. T 2 relaxation in model milk systems has been studied recently in detail by Le Dean et al [33] and Gottwald et al [34]. They showed that it is mainly controlled by the concentration of casein micelles and the dominant mechanism is proton exchange between labile protein protons and the exchange of water molecules internal to the casein micelle and in the bulk state.…”
Section: T 1 -T 2 Relaxation On Dilutionmentioning
confidence: 98%
“…T 2 relaxation in model milk systems has been studied recently in detail by le Dean et al [10] and Gottwald et al [23]. They showed that it is mainly controlled by the concentration of casein micelles and that the dominant mechanisms are proton exchange between labile protein protons and the exchange of water molecules internal to the casein micelle and the in the bulk state.…”
Section: T 1 -T 2 Relaxationmentioning
confidence: 98%